Efficacy and tolerability of telaprevir for chronic hepatitis virus C genotype 1 infection: a meta-analysis. - Yuan Kong (Public Library of Science (PLoS), 2012)
Background Chronic hepatitis C virus (HCV) infection is one of the leading causes of hepatic cirrhosis and hepatocellular carcinoma, and HCV genotype 1 is the most prevalent genotype and is resistant to current standard therapy. We performed this meta-analysis to evaluate the efficacy and safety of telaprevir-based therapy for chronic HCV genotype 1 infection. Methods We included randomized controlled trials with no year or language restriction. All data were analyzed using a random-effects model by Review Manager v5.0. The primary outcome was the proportion of patients achieving sustained virologic response (SVR), and the secondary outcomes were HCV relapse rate, incidence of severe adverse events (SAEs), and discontinuation due to adverse events. Results The proportion of achieving SVR was significantly higher in the telaprevir group (odds ratio [OR] =3.40 [1.92, 6.00], P<0.0001; I(2) =87%) regardless of a patients' previous treatment status. It was also significantly higher in the 24-week and 48-week treatment groups (OR=4.52 [2.08, 9.81], P<0.001; I(2) =85%, and OR=4.05 [1.56, 10.56], P=0.004; I(2) =92%, respectively), while it was comparable in the 12-week treatment group (OR=1.32 [0.63, 2.75], P=0.46; I(2) =35%). In addition, the HCV relapse rate was significantly reduced in the telaprevir group (OR=0.28 [0.16, 0.49], P<0.001; I(2) =76%). However, the incidence of SAE (OR=1.56 [1.15, 2.10], P=0.004; I(2) =0%) and study discontinuation due to adverse events (OR=2.24 [1.43, 3.50], P<0.001; I(2) =37%) were significantly higher in the telaprevir group. Conclusion Despite its higher incidence of SAEs and discontinuation due to adverse events, telaprevir-based therapy can increase the proportion of achieving SVR in both previously treated and untreated chronic HCV-1 infected patients.